Padepokan Karakter: A Management Model of Training and Development of Character Education - Masrukhi, Masrukhi; Munandar, Aris; Suhardiyanto , Andi (KnE Social Sciences, 2019)
Training and development of character education requires development efforts to achieve effective and maximum results. This research developed a maangement modeloftraininganddevelopmentofcharactereducationthatfocusedon Padepokan Karakter or the character hermitage as a locus, in order to produce academic, professional, and vocational resources (prospective teachers and teachers) who have excellent competence in spreading the noble character of the nation. Using Researh & DevelopmentApproach,thisresearchuseslocusatPadepokan Karakter ofthePolitics andCitizenshipDepartment,FacultyofSocialScience,SemarangStateUniversity.The subjects of the study were the newly graduated Unnes students, the junior teachers in Semarang City and Central Java Province. The factual management model of training anddevelopmentofcharactereducationthatiscurrentlyinplacecontainsweaknesses invariousaspects,fromplanning,implementation,toevaluationoftheactivities.Onthe basis of the analysis of a number of weaknesses of the factual model, a reconstruction of the conceptual model was then carried out starting from the review of both ethical and emotional factors. The conceptual model was further reﬁned by accommodating the results of focus group discussion with stakeholders so that the building of the managementmodeloftraininganddevelopmentofcharactereducation,byutilizingthe potentialsandresourcesownedby Padepokan Karakter ofthePoliticsandCitizenship Department,FacultyofSocialScience,SemarangStateUniversitywasdeveloped.This model has incorporated various aspects of training, from reﬁnement of factual model weaknesses, consideration of ethical and emotional factors, and the aspirations and needs of stake holders, making it feasible to put into trials in the wider domain. Keywords: Training management, Character education, Character hermitage